2018
DOI: 10.9734/jammr/2018/45089
|View full text |Cite
|
Sign up to set email alerts
|

Migraine among Students from the Faculty of Applied Medical Sciences, King Abdulaziz University, Jeddah, Saudi Arabia

Abstract: Methods: A cross-sectional study was done among during 2016/2017. A multi-stage stratified random sample was used, and 304 students were selected. A validated, self-administered data collection sheet was used. It included ID migraine ™, and the Migraine Disability Assessment Score

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This gender ratio of migraine prevalence was also similar to those reported in most epidemiological studies in a selected student population. 27 However, we found that the prevalence of tension-type headaches was higher among male students (38.3%) than among female students (35.0%). Lebedeva et al also found a slightly higher prevalence of tension-type headaches among male students (79.2%) than among female students (76.7%).…”
Section: Gender-related Prevalence Ratesmentioning
confidence: 54%
“…This gender ratio of migraine prevalence was also similar to those reported in most epidemiological studies in a selected student population. 27 However, we found that the prevalence of tension-type headaches was higher among male students (38.3%) than among female students (35.0%). Lebedeva et al also found a slightly higher prevalence of tension-type headaches among male students (79.2%) than among female students (76.7%).…”
Section: Gender-related Prevalence Ratesmentioning
confidence: 54%
“…Grade III is from the 11 to 20 score, which indicates moderate disability. Grade IV includes scores above 20, which indicates severe disability [ 16 - 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Migraine, as being among the neurologic illnesses, is a major public health issue because of its high frequency, accompanying disabling symptoms, and decreased function. Migraine can indeed limit people's socialization skills, work, and study at times when they are most productive (24). Migraine, the most common cause of headache in the world, is characterized by headache bouts that last anywhere from 4 to 72 hours if left untreated.…”
Section: Classifications Of Primary Headachementioning
confidence: 99%